Analiza povezanosti dejavnikov tržne naravnanosti z inovacijskimi viri na vzorcu podjetij v Sloveniji - Milfelner, Borut (Akademija MM, 2009)
In the present contribution the role and importance of market orientation for development of innovation resources is discussed. Market orientation is set ofactivities and processes that originate in adequate organizational culture. Market oriented organizations, with its information about customers and competitors and its information dissemination through relevant functions, often has better capabilities for new ideas that lever motivation for new product and new processes development. The empirical research was implemented on a sample of 415 companies with more than 20 employees in Slovenia. The results show that all three components of market orientation (customer orientation, competitor orientation and interfunctional coordination) are related with innovativeness as well as with capability to innovate.
Keywords: inovativno poslovanje; inovativnost; konkurenčnost; marketing; podjetja; Slovenia; Slovenija; trg; trženje